History and culture of Philippines, early history : the society historical background ethnicity, government, politics, economy, tourism - Jerry,Sampson (Abidjan : Sonit Education Academy, 2016)
The information on History and culture of Philippines is educational intensive and awareness for touristic value, holiday resort, and business engagements and business engagements and self-knowledge it has to do with letting people know of what they don't know about a place or something and so much need to know.
History -- Geography -- The Society -- The Economy -- Government.
Keywords: PHILIPPINES -- POLITICS AND GOVERNANCE